THE UKRAINIAN BOOK MARKET DURING THE WAR: CHALLENGES AND PROSPECTS, ADAPTATION OF MARKETING STRATEGIES AND TOOLS OF ITS SUBJECTS - PYTULYAK, Natalia; PAPROTSKA, Vita (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The dynamics and directions of development of the Ukrainian book market in modern conditions, which have their own characteristics as a result of the war, were studied. As a result of the study, it was established that the main problems of the Ukrainian book market are the devaluation of the national currency, the increase in the cost of copyright and printing services, logistical difficulties, as well as the loss of personnel due to the war. At the same time, the results of the study indicate the industry's ability to adapt, which is manifested in the diversification of formats (development of electronic and audio books), the revival of publishing activity, increased reader involvement and the restoration of the book distribution infrastructure. Particular attention is paid to the digital transformation of the industry and changes in consumer habits. It was determined that under the influence of quarantine restrictions in the conditions of COVID-19 in Ukraine, the digitalization of the industry accelerated, online trade became more active and the share of electronic publications in the overall structure of book production increased. It was established that the book market of Ukraine demonstrates moderate optimism regarding its recovery and growth in the medium term, however, it is directly dependent on the economic condition of the country and the purchasing power of the population, and requires active state intervention. The scientific novelty of the study lies in the combination of quantitative analysis of the book publishing process with the study of socio cultural trends that influence the formation of reader demand. t the same time, it has been established that there is fierce competition in the Ukrainian book market and its subjects should actively use various marketing tools in order to strengthen their competitive advantages. The practical value of the study lies in the possibility of its application by state authorities and book market participants to develop an effective strategy for supporting, strengthening and promoting the domestic publishing sector.
Keywords: Ukrainian book market; martial law; pricing in book publishing; digitalization of publishing activities; socio-cultural trends; state support for book publishing; competitive advantages